Effectiveness of methotrexate with step-down glucocorticoid remission induction (COBRA Slim) versus other intensive treatment strategies for early rheumatoid arthritis in a treat-to-target approach: 1-year results of CareRA, a randomised pragmatic open-label superiority trial. Issue 3 (18th July 2016) - Verschueren, Patrick; De Cock, Diederik; Corluy, Luk; Joos, Rik; Langenaken, Christine; Taelman, Veerle; Raeman, Frank; Ravelingien, Isabelle; Vandevyvere, Klaas; Lenaerts, Jan; Geens, Elke; Geusens, Piet; et al.
Abstract : Objectives: Combining disease-modifying antirheumatic drugs (DMARDs) with glucocorticoids (GCs) is an effective treatment strategy for early rheumatoid arthritis (ERA), yet the ideal schedule and feasibility in daily practice are debated. We evaluated different DMARD combinations and GC remission induction schemes in poor prognosis patients; and methotrexate (MTX) with or without GC remission induction in good prognosis patients, during the first treatment year. Methods: The Care in ERA (CareRA) trial is a 2-year investigator-initiated randomised pragmatic open-label superiority trial comparing remission induction regimens in a treat-to-target approach. DMARD-inexperienced patients with ERA were stratified into a high-risk or low-risk group based upon presence of erosions, disease activity, rheumatoid factor and anticitrullinated protein antibodies. High-risk patients were randomised to a COBRA Classic (MTX + sulfasalazine + prednisone step-down from 60 mg), COBRA Slim (MTX + prednisone step-down from 30 mg) or COBRA Avant Garde (MTX + leflunomide + prednisone step-down from 30 mg) scheme. Low-risk patients were randomised to MTX tight step-up (MTX-TSU) or COBRA Slim. Primary outcome was the proportion of patients in 28 joint disease activity score calculated with C-reactive protein remission at week 52 in an intention-to-treat analysis. Secondary outcomes were safety and effectiveness (ClinicalTrial.gov identifier NCT01172639 ). Results: 98 COBRA Classic, 98 COBRA Slim (high risk), 93 COBRA Avant Garde, 47 MTX-TSU and 43 COBRA Slim (low risk) patients were evaluated. Remission was achieved in 64.3% (63/98) COBRA Classic, 60.2% (59/98) COBRA Slim (high risk) and 62.4% (58/93) COBRA Avant Garde patients at W52 (p=0.840); and in 57.4% (27/47) MTX-TSU and 67.4% (29/43) COBRA Slim (low risk) patients (p=0.329). Less adverse events occurred per patient with COBRA Slim (high risk) compared with COBRA Classic or COBRA Avant Garde (p=0.038). Adverse events were similar in MTX-TSU and COBRA Slim (low risk) patients (p=0.871). At W52, 76.0% patients were on DMARD monotherapy, 5.2% used GCs and 7.5% biologicals. Conclusions: MTX with a moderate-dose GC remission induction scheme (COBRA Slim) seems an effective, safe, low-cost and feasible initial treatment strategy for patients with ERA regardless of their prognostic profile, provided a treat-to-target approach is followed. Trial registration numbers: EudraCT-number 2008-007225-39 and NCT01172639 ; Results.